Association between weight-adjusted waist circumference index and depression in older patients with hypertension: a study based on NHANES 2007–2016 - Niu, Yi; Sun, Yuqin; Xie, Yijie; Yu, Shun (Frontiers in Public Health, 2024)
Objective Our aim was to assess the relationship between weight-adjusted waist circumference index (WWI) and the prevalence of depression in older adult hypertensive patients in the United States. Methods We selected individuals from the National Health and Nutrition Examination Survey (NHANES) database from 2007 to 2016 and used logistic regression analyses, subgroup analyses, and dose–response curves to assess the associations between the WWI index and the prevalence of depression in older hypertensive patients with age, sex, and BMI. Results A total of 4,228 participants aged ≥60 years with hypertension were included in our study; 364 patients were assessed for depression. After correction for confounders, each unit increase in WWI increased the risk of depression in older hypertensive patients by 19% (OR = 1.19, 95% CI: 0.99, 1.43). Dose–response curves showed that the WWI index was positively associated with the prevalence of depression in older hypertensive patients when the WWI index was ≥11.6. Based on subgroup analyses, this association was particularly pronounced in individuals ≥70 years of age, women, and individuals with a BMI of 25 or greater. Conclusion Higher WWI scores were positively associated with the prevalence of depression in older hypertensive patients and correlated with gender, age and BMI. This is notable, although a causal relationship cannot be established at this time.